PREVALENCE, AWARENESS AND CONTROL OF HYPERTENSION WITH OFFICE BLOOD PRESSURE MEASUREMENTS AND AMBULATORY BLOOD PRESSURE MONITORING IN KIDNEY TRANSPLANT RECIPIENTS. (April 2021) - Loutradis, Charalampos; Korogiannou, Maria; Xagas, Efstathios; Marinaki, Smaragdi; Argyris, Antonios; Protogerou, Athanasios; Sarafidis, Pantelis; Boletis, John
Abstract : Objective: The prevalence of hypertension in patients with chronic kidney disease (CKD) is estimated to 80–90% as determined by ambulatory blood pressure monitoring (ABPM), while adequate control is achieved in only 20–30% of these patients. Until now, few reliable data exist on the prevalence and blood pressure (BP) control in kidney transplant recipients, as determined by ABPM. The objective of this study is to examine these epidemiologic characteristics of hypertension in kidney transplant recipients using ABPM. Design and method: 150 kidney transplant recipients were included in this study. They underwent 24-hour ABPM with the Mobil-O-Graph NG device. Hypertension was defined as follows: (1) office BP (oBP) > or = 140/90 mmHg or use of antihypertensive agents, (2) ambulatory BP > or = 130/80 mmHg or use of antihypertensive agents. Awareness of arterial hypertension was determined according to their past medical history. Adequate control was defined as oBP <140/90 or 24-hr BP <130/80 mmHg. Results: Prevalence of hypertension was 88.0% according to office BP measurements and 93.3% according to ABPM data (p = 0, 112 and kappa-statistics = 0, 531, p < 0, 001). Totally, 26, 7% had office BP > or = 140/90 and 58, 7% 24-hr BP > or = 130/80 mmHg (p < 0, 001). Awareness of arterial hypertension was 88, 6% irrespectively of the method (p = 0, 987).83.3% of the patients were receiving antihypertensive agents. Adequate control according to office BP measurements had 69, 7% of the hypertensive patients, whereas only the 37.1% of them achieved adequate control according to ABPM (p < 0, 001 and kappa-statistics = 0, 205, p = 0, 005). In hypertensive patients, office BP > or = 140/90 mmHg was of poor predictive value in the diagnosis of 24-hour BP > or = 130/80 mmHg (AUC: 0, 590, 95%CI: 0, 499–0, 681, sensitivity: 34, 1%, specificity: 83, 9%, positive predictive value: 75, 0%, negative predictive value: 47, 3%). Conclusions: The prevalence of arterial hypertension in kidney transplant recipients is extremely high. Office BP readings is a poor marker for assessment of BP control, as there appears to be a huge difference between office and ABPM in the rates of hypertension control.